The Effect of Moving and Fixed Target Training on The Accuracy of Gyaku-Tsuki Punches Karate Athletes - Manullang, Jujur Gunawan; Arvan Junaidi , Ilham; Hermanysah, Bambang; Imansyah, Farizal; Antariningsih, Ning (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
The purpose of this study is to examine the effect of fixed target training and moving on the accuracy of gyaku-tsuki punches in karate athletes at PGRI Palembang University. This research is carried out in the form of pseudo-experimental research with experimental methods. The subjects of the study were 60 karate athletes from PGRI Palembang University. The instrument used is the precision of the gyaku-tsuki punch. Data analysis techniques use hypothesis tests with t-test analysis (paired sample t test). Based on the results of the paired t test analysis, the first t test sample has obtained an F value of 0.099 > sig. 0.05. Based on the percentage increase in accuracy results, it is known that accuracy with moving target training has a greater increase than training using fixed targets. Based on these results, it can be concluded that there is an effect of fixed target training and moving on the accuracy of gyaku-tsuki punches in PGRI Palembang University karate athletes, and the percentage of accuracy increase with moving target training has a greater increase than regular training.